Proyecto sobre el diseño de un reel creativo para laborar en medios visuales. - Andino, Patricio (2010)
This project has released a breakthrough product called Reel Creative (Video CD) for people who range from 15 to 30 years of age both men and women who wish to venture into visual media. Assigning three levels of presentation such as: Basic Level, Intermediate level and Advanced Level. You can skip to the law firms (producers, television channels) that have several years of experience where, through surveys we obtained a 90% claim to know that working with creative Reels to ignore a company that is dedicated to this service. In the case of natural persons was obtained as a result a level of acceptance of 95%. It develops the technical manual describing the product which is the Reel Creative, focused on individuals interested in working in visual media, classifying 3 levels of acceptance which include 4 types of services: Description of the person, mention of a product, sketch and photo session. Showing the total operating expenditures reaching $ 60,220.00 total investment of Reel Creative, within these operating expenses are included initial capital expenditure, working capital and advertising. Found throughout the research for the future operation of the proposed development of Reels creative work in visual media.